The effect of diet and age-at-weaning on growth and survival of clownfish Amphiprion percula (Pisces : Pomacentridae) - Gordon, Andrew K (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1999)
The aim of this study was to improve the rearing of common clownfish Amphiprion percula, by weaning juveniles from a live feed to a formulated feed as early as possible, while still maintaining good growth and survival. The growth response of A. percula to a formulated dry feed was initially investigated. There was no difference in growth rate of juveniles fed a formulated feed, and the formulated feed supplemented with either Artemia or a Donax serra / Penaeus indicus combination. Amphiprion percula readily consumed the formulated feed, and the fishmeal/casein combination appeared an acceptable protein source. As the amount of protein included in a diet can have a profound effect on growth, the optimal dietary protein level for juvenile A. percula was investigated by feeding semipurified diets containing graded levels of protein, ranging from 40-65%. There was no difference in the growth rates of juveniles fed the various diets, however all diets promoted good growth with an average weight gain of 419%, and thus for the purposes of this study the diet formulation was deemed adequate. The histological study of the digestive system of larval A. percula revealed that the alimentary canal was advanced at hatching and that larvae start exogenous feeding immediately. Three days after hatch (DAH) the yolk sac is completely absorbed. In the hind-gut epithelium of 5-day-old larvae small supranuclear inclusion vacuoles appear, suggesting pinocytotic digestion, and by 7 DAH gastric glands are established in the epithelium of the stomach. Nine DAH supranuclear inclusion vacuoles appear in the epithelium of the mid-gut, indicating extracellular digestion and absorption across the lumen. As pinocytotic digestion of protein is less efficient than extracellular digestion, especially in the case of formulated feeds, it was hypothesised that the digestive system of A. percula could only effectively digest formulated feeds 9 DAH onwards. The two weaning experiments designed to test this hypothesis revealed that A. percula was able to utilise the formulated feed, without reduction in survival, from 7 DAH onwards. However, in terms of growth, the optimal time to wean juveniles from the live feed to the formulated dry feed was between 15 to 20 DAH. As A. percula accept a formulated feed and can benefit nutritionally from it, the dependence of larvae and juveniles on live feed can be reduced. This study has shown that the rearing of A. percula can been simplified and improved by weaning from 7 DAH with no reduction in survival, and from 15 to 20 DAH with no reduction in growth.
Keywords: Anemonefishes; Pomacentridae; Fishes -- Growth